Nomophobia in university students during COVID-19 outbreak: a cross-sectional study - Navas-Echazarreta, Noelia; Juárez-Vela, Raúl; Subirón-Valera, Ana Belén; Rodríguez-Roca, Beatriz; Antón-Solanas, Isabel; Fernández-Rodrigo, María Teresa; de Viñaspre-Hernandez, Regina Ruiz; Sabater, Antonio Martínez; Echániz-Serrano, Emmanuel; Saus-Ortega, Carles; Santolalla-Arnedo, Iván; Satústegui-Dordá, Pedro José (Frontiers in Public Health, 2023)
Currently, access to the Internet through smartphones has led to their functions going beyond purely communicative ones, allowing the management of massive, instantaneous, and easily accessible information. This research analyzed the differences in smartphone use and the prevalence of nomophobia, mainly according to gender and university degree of Health Sciences students at the University of Zaragoza during the COVID-19 confinement in Spain. A descriptive cross-sectional study was carried out on a sample of 318 first and second grade students, who completed an online questionnaire sent to their institutional email, which included sociodemographic questions, other questions about smartphone use and the Nomophobia Questionnaire (NMP-Q) scale.. Compared to men (n=58), women (n=260) were more likely to use their smartphones more intensively daily, as were occupational therapy students compared to the other degree programs studied. The prevalence of nomophobia was moderate, being around the risk of suffering from it. No significant differences in scores for nomophobia among students were found according to gender, university degree, or population nucleus for the nomophobia scores of the students. The present study extends the existing literature on nomophobia by providing results of interest in terms of gender and the exceptional healthcare context of COVID-19. The results suggest that despite intense daily smartphone use young people did not reach severe nomophobia figures. This fact underlines the need for appropriate and healthy technology education. Understanding the characteristics of the populations that use the smartphone the most may help to analyze nomophobia rates and the massive use of the device.